2006
DOI: 10.1021/jm060686r
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Inhibitors of Human Sirtuin Type 2:  Novel Structural Scaffolds

Abstract: A successful virtual screening experiment of novel SIRT2 inhibitors is described. Four out of 11 experimentally tested compounds showed in vitro inhibitory activity toward SIRT2 in a micromolar level, resulting in an experimental hit ratio of 36%. Two of these compounds inhibited SIRT2 with IC50 (microM) values of 51 and 91; moreover, one of the new inhibitors was comprised of an entirely new SIRT2-inhibiting structural scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…Structurally different compounds have also been identified through virtual screening methods and have been reported as SIRT2 specific. [83][84][85][86] A halogenated splitomicin analog (HR73) has been reported as a selective inhibitor of SIRT1. Finally, cambinol is the only sirtuin inhibitor of which the anticancer properties have been described.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…Structurally different compounds have also been identified through virtual screening methods and have been reported as SIRT2 specific. [83][84][85][86] A halogenated splitomicin analog (HR73) has been reported as a selective inhibitor of SIRT1. Finally, cambinol is the only sirtuin inhibitor of which the anticancer properties have been described.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…Combination of in-silico methodologies and biochemical in vivo assays resulted in the identification of further SIRT2 inhibitors with diverse scaffolds 96,119,120 with moderate potencies, for example compound 21 (see Fig. 13).…”
Section: Structural Diverse Sirtuin Inhibitorsmentioning
confidence: 99%
“…Using the same approach Poso et al performed further virtual screening campaigns on other compound libraries. 119,120,122 Several moderately active inhibitors could be identified from the Leadquest and Maybridge compound collections.…”
Section: Computer-based Identification Of Sirtuin Modulatorsmentioning
confidence: 99%
“…The pseudo-spiro compound 31, a moderately active Sirt2 inhibitor, has been identified by an in silico approach [119]. A crystal structure of the poly-sulfonylated symmetric urea suramin 32 bound to the catalytic site of Sirt5 has been elucidated [110] and demonstrated that the poly-aromatic compound covers the Although suramin is unlikely to be brain permeable due to its size and highly negatively charged functionalities, the five last scaffolds display interesting characteristics: the diphenol 33, the indanone 34, and the tetrahydroisoquinoline 35 have been discovered by high throughput screening [120].…”
Section: Sirtuin Inhibitorsmentioning
confidence: 99%